Evaluation of User Satisfaction and Loyalty of Sports News Portal Application Using Technology Acceptance Model - Saputra, Roy Inzaqhi; Haryamadha, Rama; Nuryasin, Ilyas (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Current technological advances have created gaps in people's ability to obtain information quickly. It was as if the strenuous efforts of people wanting to know more about what had happened had broken down the information barrier. This research is included in the category of quantitative descriptive research. This research is focused on news portal application users. The sampling technique used in this study was random sampling, with a total sample of 100 participants. This research uses PLS data analysis technique with SEM approach model. The results showed that perceived ease of use affects mobile user satisfaction. Perceived usefullness affects mobile user satisfaction. Trust affects mobile user satisfaction. Convencience affects mobile user satisfaction. Security affects mobile user satisfaction. Perceived ease of use does not affect user loyalty. Perceived usefullness affects user loyalty. Trust affects user loyalty. Convencience affects user loyalty. Security affects user loyalty.